Deconstructing the moral mind: when data speak - Olivera-La Rosa, Antonio (Revista Colombiana de Ciencias Sociales, 2014)
The study of the psychological foundations of moral judgments has gone beyond the merely theoretical treatment to constitute an empirical academic subject. Although studies of moral topics have been ubiquitous in both humanities and social sciences, it is not until the integration of different scientific disciplines in the convergent science of moral psychology that the study of morality seems to start its flourishing age. © Revista Colombiana de Ciencias Sociales.